Functional diets improve survival and physiological response of Atlantic salmon (Salmo salar) to amoebic gill disease - Mullins, J; Barbara Nowak; Melanie Leef; Ron, O; Eriksen, TB; McGurk, C (2020)
Amoebic gill disease (AGD) is a major challenge for the marine salmonid farming industry. This disease is caused by Paramoeba perurans , which is a parasitic amoeba that affects fish growth and survival. The present work aimed at improving Atlantic salmon ( Salmo salar ) diet formulation as a preventive treatment for AGD. Four diets with different quantitative composition of functional ingredients, such as arginine, premixes, plant extracts, nucleotides, beta glucans, and vitamins C and E were tested. In the first trial, fish fed the different diets were exposed to a 74‐day challenge trial with P. perurans , and their survival, feed intake, and growth performance were analyzed together with plasma properties and gill histopathology. Additionally, a second trial was performed where mucus constituents of Atlantic salmon fed the same diets were analyzed from fish that were not exposed to AGD. Results suggest a positive effect of the functional ingredients on Atlantic salmon survival and immune response. Particularly, the inclusion of arginine, microadditives, and vitamins C and E improved survival, with arginine being an important driver of pathogen protection. The protective role of mucus also improved with these functional ingredients in nonchallenged fish, as suggested by its greater viscosity and by the increased levels of lysozymes and polysaccharides. Overall, the present work supports improving diet formulation as a promising approach for the preventive treatment of AGD.